Experimental and Numerical Studies of Natural Convection on Elliptical Tube in Thermal Asymmetric Cavity - Angga Tegar Setiawan; Budi Utomo Kukuh Widodo; Nila Rahmawati (JMES: The International Journal of Mechanical Engineering and Sciences, 2018)
The characteristic of natural convection heat transfer in a thermally asymmetric cavity is influenced by temperature differences and space between the heat source and cavity wall. The heat source is any bluff body placed inside the cavity. This research used a heated elliptic tube as the heat source inside the cavity. The three tubes are of 2.5 aspect ratio (AR) in a vertically aligned arrangement. The cavity was thermally asymmetric because three sides of the cavity were insulated while the other side was exposed to convection with ambient air. The clearance ratio (CR) as the ratio between the gap from the insulated wall to the major axis of the tubes to the space of the cavity is varied 0.4 and 0.6. while the pitch ratio is constant at 3.5a. this study analyzes the characteristics of heat transfer from the surface of the elliptical tube to the surrounding air experimentally and numerically. The result reveals that the highest heat transfer coefficient 0f 0.4 CR is higher than that of 0.6 CR. The numerical solution shows the contour and streamlines of the fluid flow in all conditions as the characteristics of natural transfer thermally asymmetric cavity.